Nuclear cell-free DNA on the loose: an early warning signal of ischemia–reperfusion injury in kidney transplantation - Strandberg, Gabriel; Trattner, Rebecca; Martin, Myriam; Öberg, Carl M.; Raihle, Carl; Slivca, Oleg; Alam, Shahnawaz; Segelmark, Mårten; Christensson, Anders; Nilsson, Bo; Paul, Clara; Blom, Anna M.; et al. (Frontiers in Immunology, 2026)
IntroductionCell-free DNA is an emerging marker of allograft injury, yet its role in the immediate phase of ischemia–reperfusion injury remains incompletely understood.MethodsIn this prospective cohort of 127 kidney transplant recipients (86 deceased donors, 41 living donors), intraoperative plasma samples were collected systemically pre-implantation and from the allograft vein postreperfusion. Nuclear and mitochondrial cell-free DNA were quantified, alongside subset assessments of neutrophil extracellular trap markers and soluble C5b-9 as a marker of thromboinflammation. An in vitro necrosis model of human proximal tubular cells evaluated the concordance between cell injury and C5b-9 generation.ResultsAn immediate and sustained release of nuclear, but not mitochondrial, cell-free DNA was observed post-reperfusion, predominantly in deceased donor kidneys. This release corresponded with cold ischemic time and delayed graft function while showing temporal correlations with soluble C5b-9, indicating that cell-free DNA release parallels thromboinflammatory activation upon reperfusion. In vitro, C5b-9 generation occurred on necrotic, but not viable, tubular cells, supporting the relationship between cell injury and thromboinflammation. Neutrophil extracellular trap markers did not consistently correlate with early cell-free DNA release.ConclusionImmediate nuclear cellfree DNA release upon reperfusion reflects intragraft injury linked to downstream thromboinflammatory activation, underscoring the impact of early ischemia–reperfusion injury.